2023
DOI: 10.1186/s40168-023-01578-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome modulates tacrolimus pharmacokinetics through the transcriptional regulation of ABCB1

Abstract: Background Following solid organ transplantation, tacrolimus (TAC) is an essential drug in the immunosuppressive strategy. Its use constitutes a challenge due to its narrow therapeutic index and its high inter- and intra-pharmacokinetic (PK) variability. As the contribution of the gut microbiota to drug metabolism is now emerging, it might be explored as one of the factors explaining TAC PK variability. Herein, we explored the consequences of TAC administration on the gut microbiota composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“… 10 Abcb1a can be differentially expressed between germ-free (GF) and conventionally raised (CONV-R) mice 11 , 12 ; however, a recent study failed to detect a significant difference in Abcb1a transcript levels. 13 Variation in the specific gut microbiota found between facilities could provide one potential reason for these discrepant results, consistent with experiments administering single pathogenic, probiotic, and commensal bacteria that can tune Abcb1a expression in either direction, 11 , 14 , 15 , 16 experiments with broad-spectrum antibiotics, 17 and a study implicating butyrate-producing bacteria in colonic P-gp protein levels. 18 More importantly, the functional consequences of microbiota-driven changes in Abcb1a expression and the mechanisms responsible remain largely unexplored, with the exception of a recent paper implicating microbiota-dependent induction of Abcb1a expression in tacrolimus pharmacokinetics.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“… 10 Abcb1a can be differentially expressed between germ-free (GF) and conventionally raised (CONV-R) mice 11 , 12 ; however, a recent study failed to detect a significant difference in Abcb1a transcript levels. 13 Variation in the specific gut microbiota found between facilities could provide one potential reason for these discrepant results, consistent with experiments administering single pathogenic, probiotic, and commensal bacteria that can tune Abcb1a expression in either direction, 11 , 14 , 15 , 16 experiments with broad-spectrum antibiotics, 17 and a study implicating butyrate-producing bacteria in colonic P-gp protein levels. 18 More importantly, the functional consequences of microbiota-driven changes in Abcb1a expression and the mechanisms responsible remain largely unexplored, with the exception of a recent paper implicating microbiota-dependent induction of Abcb1a expression in tacrolimus pharmacokinetics.…”
Section: Introductionmentioning
confidence: 56%
“… 18 More importantly, the functional consequences of microbiota-driven changes in Abcb1a expression and the mechanisms responsible remain largely unexplored, with the exception of a recent paper implicating microbiota-dependent induction of Abcb1a expression in tacrolimus pharmacokinetics. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Building on prior research that highlighted the influence of microbial metabolism on the efficacy and toxicity of immunosuppressive drugs (20,21), our study further elucidates how gut microbiota can modify drug responses both locally and systemically. We demonstrated that bacteria can activate the prodrug MMF into its active form, mirroring the host's prodrug activation.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, upon antibiotic treatment, TAC exposure increased in a manner totally reversible with the ABC1B1 blocker zosuquidar. While the study by Guo et al [ 25 ] seem to suggest that fecal microbiota reduces TAC bioavailability, the data reported by Degraeve et al (2023) [ 124 ] seem to propend for the opposite scenario of intestinal bacteria enhancing TAC absorption. The inconsistent findings of these two studies (one performed in man and the other in mice) leave open the question of how the intestinal microbiota affects TAC pharmacokinetics and whether species-specific factors are involved.…”
Section: Discussionmentioning
confidence: 99%